Gamified English Instruction and Multidimensional Student Engagement: Investigating Temporal Acceleration in Upper Primary EFL Classrooms - Irsani, Rahmita; Dollah, Syarifuddin; Muhayyang, Maemuna; Sunra, La (STAIN Majene, 2026)
Despite growing scholarly interest in gamification as a pedagogical strategy, existing research relies heavily on quantitative measures test score, participant rates, and survey instruments that reveal little about how students actually experience gamified environments. This study investigates how upper primary EFL students in an Islamic school setting in Indonesia experience gamified English instruction, and what dimensions of engagement emerge from that experience. Drawing on classroom observations, semi-structured interviews, and teacher-written reflective journals involving twelve students from grades 4 through 6 and two experienced English teachers, the study captures the texture of day-to-day engagement with Wordwall and Kahoot over a sustained instructional period. Utilizing Thematic analysis revealed four interrelated dimensions: a noticeable sharpening of behavioral participation and on-task effort; emotional transformation marked by enthusiasm and competitive anxiety; a strategic cognitive effort beyond surface level game playing; and recurring reports of temporal acceleration, interpreted as indicative of flow states. Reading these findings through the lens of self-determination theory and the multidimensional engagement framework, the study argues that gamification functions as a psychological activator rather than a mere motivational add-on. These findings suggest that when thoughtfully integrated, gamified instruction has the potential to deepen genuine learner engagement; however, future research must examine whether such engagement translates into durable linguistic gains.